Thermodynamic characterization of solidification and defects that occur in Mg-alloy AM60 - Vončina M.; Petrič M.; Mrvar P.; Medved J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The AM60 alloy was thermodynamically examined using chemical analysis, thermodynamic calculation made by ThermoCalc program, “in situ” thermal analysis and differential scanning calorimetry (DSC), whereas the microstructure constituents were confirmed using optical and scanning electron microscopy (SEM). At the eutectic temperature of 437 °C the equilibrium solubility of Al in Mg is 12.6 wt. % Al. On the boundaries of the primary Mg grains the intermetallic compound of Al12Mg17 is precipitating according to the solvus line of the Mg-Al phase diagram. Solidification of the AM60 alloy has been investigated using “in situ” simple thermal analysis. The investigation of solidification has been taking place by evaluation of the cooling curves in connection with metallographic examinations, differential scanning calorimetry and thermodynamic calculations. All defects, nonmetallic inclusions and intermetallic compounds that occur in investigated AM60 alloy were identified.